The Effect Of Work-Life Balance On Employee Burnout At PT. Advantage Service And Cash Management (Scm) Bengkulu - Bella, Ulvia; Gayatri, Ida Ayu Made Er Meytha; Indriasari, Nia (Utami Publisher, 2026)
Burnout is a condition of physical, emotional, and mental exhaustion caused by prolonged stress at work. Work-life balance is an important aspect in creating a balance between work demands and personal life. The purpose of this study is to determine the effect of work-life balance on employee burnout at PT. Advantage SCM Bengkulu. Work-life balance is a state of balance in two demands where an individual's work and life are the same. Burnout is a state of extreme psychological stress that causes an individual to experience emotional exhaustion and low motivation to work. This research method uses quantitative descriptive research. This research was conducted at PT. Advantage SCM Bengkulu with a sample of 60 people with a sampling technique in this study using total sampling. The data collection technique is a questionnaire. The data analysis technique used in this study is quantitative descriptive. The results of the study indicate a significant influence between work-life balance on burnout with a calculated t value of 5.846 > t table 1.67203 and a sig a value of 0.000 < 0.050.